Prostate Adenocarcinoma With Atypical Immunohistochemistry Presenting With a Cheerio Sign - Creticus Marak; Achuta Kumar Guddati; Adrita Ashraf; James Smith; Prashant Kaushik (Annals of Internal Medicine: Clinical Cases)
The most common cancer in men is prostate cancer. The Cheerio sign is the computed tomography finding of multiple pulmonary nodules with central lucency resembling the ring-shaped Cheerio breakfast cereal. Unlike bone metastasis, pulmonary involvement is less common. The Cheerio sign has malignant and benign etiologies. Thyroid transcription factor-1 (TTF-1) stain is commonly used in the diagnosis of primary lung cancer. TTF-1 positivity in cancers of prostate origin is rare, with only case reports and small case series available in the literature. Metastatic prostate cancer presenting with a Cheerio sign has not been reported in the literature.